Case Report: Rare meets rare—miliary prostate cancer brain metastasis - Gill, Jaspreet K.; Detsky, Jay; Golan, Eyal; Yeung, Robert; Shiner, Audrey; Emmenegger, Urban (Frontiers in Oncology, 2025)
IntroductionMiliary brain metastasis (MM), consisting of innumerable miliary lesions in perivascular location, is a rare disease entity with an estimated incidence of 3.8% among patients with brain metastasis (BM). Similarly, with an approximated incidence of less than 2%, prostate cancer (PC)-related BM is also an infrequent presentation; however, it is more common in patients with neuroendocrine differentiation. To the best of our knowledge, only one other case of MM secondary to PC has been reported. This case report discusses two additional cases of PC-related MM, a condition otherwise predominantly observed secondary to pulmonary adenocarcinoma.Case presentationsThe first case describes a patient in his 60s known for metastatic PC with suspected neuroendocrine differentiation and presenting with musculoskeletal pain, lethargy, and status epilepticus. Contrast-enhanced computer tomography (CT) angiogram and magnetic resonance imaging (MRI) of the head and neck revealed diffuse and innumerable foci in the cerebral hemispheres, brainstem, and cerebellum. The second case discusses a similarly aged male patient with biopsy-proven de novo mixed adenocarcinoma/small cell neuroendocrine PC and with symptoms consisting of significant weakness, aphasia, confusion, and decreased level of consciousness. Non-contrast-enhanced CT imaging of the brain did not reveal MM; however, a follow-up contrast-enhanced MRI detailed miliary lesions in the cortex, white matter, deep gray nuclei, brainstem, and cerebellum. Both patients expired within a couple of weeks from admission.ConclusionGiven its rarity, notably in patients with PC, there are no specific and established diagnostic criteria for MM, a condition with ominous prognosis seemingly related to neuroendocrine differentiation in men with PC.